Development of performance management system incorporating dual perspectives of enterprise and customers'. Issue 3 (12th July 2018) - Yadav, Neetu; , Sushil; Bititci, Umit Sezer
Abstract : Purpose: Performance measurement and management (PMM) literature is highly abundant with numerous PMM frameworks encapsulating various aspects of enterprise performance that are largely driven by enterprise viewpoint. Considering dynamic nature of Indian telecom industry where customers hold high bargaining power in the industry, flexible strategy game-card has been adopted as a theoretical basis. The purpose of this study is to capture an "outside-in view" of enterprise performance by incorporating performance measurement from customers' perspective and highlight dual perspectives of performance, i.e. enterprise and customers'. Design/methodology/approach: Rigorous empirical data analysis tools have been used on the data collated through opinion survey to develop strategic performance management model for Indian telecom service providers where mediation effects of customers'-based strategic factors have also been captured. Findings: The findings emphasize the fact that financial performance indicators are outcome variables that are driven by the external environment, internal organizational structure and business processes. An effective performance management system (PMS) should consist enabling performance indicators (customers' perspective) in addition to leading and lagging performance indicators that are widely discussed in the literature. Research limitations/implications: The set of performance indicators identified is in the context of Indian telecom service operators, which should be used in another context with full caution. The generalization of the empirically validated strategic performance management model in other country context is limited. However, the process of development of PMS could be taken as an example to replicate in any other context. Originality/value: Measuring an enterprise performance from customers' perspective is the major contribution of this study. With the diverse set of performance indicators, effective PMS can be developed and deployed where tangible measures act as lagging indicators, namely, situational and operational, strategic measures act as leading indicators, and subscribers' crucial assessment measures act as enabling indicators.